Teaching the Analysis of Newton’s Cooling Model to Engineering Students - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2023)
To apply mathematical methods to physical or other real life problem, we have to formulate the problem in mathematical terms. It means that, we have to construct the mathematical model for the problem. Many physical problems shows the relationships between changing quantities. The rates of change are represented mathematically by derivatives. In this case the mathematical models involve equations relating an unknown function and one or more of its derivatives. These equations are the differential equations. In this article, teaching the analysis of Newton’s cooling model to engineering students is presented as one of the applications of separable differential equations.